2011
DOI: 10.1002/prot.23238
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of a signal peptide in complex with signal peptidase I cytoplasmic domain: The stabilizing effect of membrane‐mimetics on the acquired fold

Abstract: A protein destined for export from the cell cytoplasm is synthesized as a preprotein with an amino-terminal signal peptide. In Escherichia coli, signal peptides that guide preproteins into the SecYEG protein conduction channel are typically subsequently removed by signal peptidase I. To understand the mechanism of this critical step, we have assessed the conformation of the signal peptide when bound to signal peptidase by solution NMR. We employed a soluble form of signal peptidase without its two transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The helix-breaking M26P mutation supports our conclusion that lack of co-translational Env signal-peptide cleavage is primarily the result of secondary structure around the cleavage site. NMR studies of E.coli signal peptidase in complex with alkaline phosphatase signal peptide revealed that the cleavage region adopted a poorly structured ‘U-turn’ shape ( De Bona et al, 2012 ). The loop originated from proline in position −5 to the cleavage site confirming the role of proline in separating hydrophobic and C-terminal region of signal peptides by inducing formation of unstructured turns or loops predicted in the literature earlier ( von Heijne, 1983 ; Jain et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…The helix-breaking M26P mutation supports our conclusion that lack of co-translational Env signal-peptide cleavage is primarily the result of secondary structure around the cleavage site. NMR studies of E.coli signal peptidase in complex with alkaline phosphatase signal peptide revealed that the cleavage region adopted a poorly structured ‘U-turn’ shape ( De Bona et al, 2012 ). The loop originated from proline in position −5 to the cleavage site confirming the role of proline in separating hydrophobic and C-terminal region of signal peptides by inducing formation of unstructured turns or loops predicted in the literature earlier ( von Heijne, 1983 ; Jain et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positioned at the N‐terminus of secreted proteins, signal peptides in E. coli must be recognised by either SRP or SecA if they are to be targeted to the translocon. The flexibility of the C‐terminal end of the signal‐peptide, often rich in structure‐disrupting residues such as proline and glycine, was thought to facilitate access by signal peptidases I and II (De Bona et al , 2012). However, Smets et al (2022) demonstrate a novel function for this region in disrupting the folding of downstream regions (Fig 1E).…”
Section: Figure Folding‐dependent Protein Translocation Across the Pl...mentioning
confidence: 99%
“…Alternatively, mutating a proline (P71) on the C-terminal side of the cleavage site does not have a significant effect on σ V activity suggesting the proline at position 61 has a role in site-1 processing. It is thought this residue is important for creating a U turn in the structure that creates disorder at positions -5 to -1, thus arranging them to interact with the signal peptidase active site (Auclair et al, 2012;; Bona et al, 2012). It is also thought this residue stops the formation of the helix from the transmembrane domain, which contributes to positioning the signal peptidase cleavage site close to the membrane and signal peptidase (Auclair et al, 2011;; Bona et al, 2012).…”
Section: Analyzing Constitutive Rsiv Mutantsmentioning
confidence: 99%